Kreasi Motif Printing Ornamen Rumah Limas dan Kain Semi Songket Palembang pada Ready to Wear Deluxe - Nisrina Iftinan Dhia; M Tavip; Haidarsyah Dwi Albahi (ATRAT: Jurnal Seni Rupa, 2025)
The development of the fashion world, especially in ready to wear deluxe, is currently closely related to technology, one of them is digital printing technology. Based on that, the idea was born from the interior ornaments of "Limas" house (Palembang traditional house) to be used as fabric printing motif. This ready to wear deluxe idea will be combined with Palembang semi songkat fabric so that it fulfills the principle of creating ready to wear deluxe itself. This creation has several stages, such as exploration, design, and realization. The purposes of this work are; (1) as a form of appreciation for one of Palembang's cultures (2) as a reference for designers in creating a fashion collection. The result of this creative process is 3 (three) deluxe ready to wear looks presented at Jogja Fashion Parade 2024.